Energy loss of helium ions in zinc - Lantschner, G.H. (2004)
The energy loss of helium ions in zinc has been measured in the energy range from 37.5 to 1750 keV/amu using the transmission technique and the Rutherford backscattering method. In addition, calculations using the extended Friedel sum rule, the unitary convolution approximation, and the local plasma approximation have been performed. The contributions of the inner-shell and valence electrons to the total energy loss are separately evaluated. The measurements and calculations are in good agreement over an extended range of energies, and both of them yield stopping values higher than those provided by SRIM 2003.